P568 Bowel ultrasonography is useful to evaluate disease activity in ulcerative colitis patients. (25th January 2019) - Takahashi, S; Hirano, Y; Izumikawa, K; Colvin, H; Colvin, M; Kagawa, T; Aoyama, Y; Matsueda, M; Kawai, Y; Okamoto, K; Sakakihara, I; Yamamoto, K; et al.
Abstract: Background: Colonoscopy (CS) is the gold standard for evaluating disease activity in ulcerative colitis (UC). However, CS is invasive and especially so for patients with severe UC. We therefore evaluated the usefulness of bowel ultrasonography (BUS), as a non-invasive and potentially cost-effective alternative to CS. Methods: UC patients followed at Kagawa Prefectural Central Hospital from September 2014 to August 2018 were included in this study. One gastroenterologist performed BUS, and the UC-BUS Grade was scored from 0 to 4 at six segments of the large bowel: caecum, ascending colon, transverse colon, descending colon, sigmoid colon and rectum based on colonic wall thickness, structure and irregularity. Right after BUS, a different gastroenterologist performed CS and the Mayo Endoscopic Score (MES) was scored from 0 to 3 at the six segments of the large bowel mentioned above. The Spearman's rank correlation was calculated at each of the large bowel segments. Results: A cumulative total of 230 UC patients (73 women and 157 men) were prospectively included. The median patient age at examinations was 45.5 years (range, 13–82 years). The highest MES in the six segments was as follows: MES 0: 61 patients, MES 1: 60 patients, MES 2: 54 patients and MES 3: 55 patients. The success rate of ultrasound visualisation was 100% (230/230) in the caecum, ascending colon, transverse and sigmoid colon, and 99.6%(229/230) in the descending colon, and 96.5% in the sigmoid colon. Spearman's rank correlation was 0.32 (caecum), 0.56 (ascending colon), 0.52 (transverse colon), 0.55 (descending colon), 0.61 (sigmoid colon), 0.52 (rectum) and 0.56 (all segments) ( p < 0.0001 in all segments). Conclusions: BUS is useful to evaluate disease activity in all the segments of the large bowel of UC patients.